2014
DOI: 10.1021/bm5015427
|View full text |Cite
|
Sign up to set email alerts
|

Why do Some Immobilized N-Alkylated Polyethylenimines Far Surpass Others in Inactivating Influenza Viruses?

Abstract: A number of N-alkylated polyethylenimines (PEIs) were covalently attached to glass-slide surfaces, and their virucidal efficacies against three different strains of influenza viruses were examined quantitatively. The anti-influenza activities of the modified surfaces varied widely, with the most potent, immobilized N,N-hexyl,methyl-PEI and N,N-dodecyl,methyl-PEI, reducing the viral titer by over three logs (i.e., >99.9%). While the virucidal activities of the glass surfaces derivatized with N-alkylated PEIs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…[ 66–69 ] Regarding the first group of non‐leaching contact‐killing polymers, an intense research has been carried out by Klibanov's group at the MIT on hydrophobic polyethyleneimine (PEI) derivatives. [ 61,70–72 ] These polymer coatings can be non‐covalently deposited on a variety of solid surfaces (plastics, glass, fabrics, bandages, etc.) by spraying, brushing, or dipping, leading to virucidal materials.…”
Section: General Aspects Of the Interaction Of Viral Particles With Smentioning
confidence: 99%
“…[ 66–69 ] Regarding the first group of non‐leaching contact‐killing polymers, an intense research has been carried out by Klibanov's group at the MIT on hydrophobic polyethyleneimine (PEI) derivatives. [ 61,70–72 ] These polymer coatings can be non‐covalently deposited on a variety of solid surfaces (plastics, glass, fabrics, bandages, etc.) by spraying, brushing, or dipping, leading to virucidal materials.…”
Section: General Aspects Of the Interaction Of Viral Particles With Smentioning
confidence: 99%
“…Further, it was indicated that the penetration mechanism was facilitated by the flattened antimicrobial polymer brushes on the surface . it was also shown that a higher density of the immobilized quaternary ammonium groups on the surfaces accessible to pathogens was the determining factor of the potency; and similar observation was obtained for the membrane containing imidazolium units . The mechanisms of the disruptions of the cell membranes of pathogens might depend on the chemistry, topology, and morphology of antimicrobial polymers fixed on the surfaces.…”
Section: Introductionmentioning
confidence: 81%
“…It should be meaningful to develop polymers with optimal spatial distribution of antimicrobial units, such as amines, peptides and other potent species, to explore the different distribution of negative charges on the cell membranes of pathogens and human cells. Although it was indicated that the charge density of polymers on the surfaces needs to be higher than a threshold value and is a key factor to achieve antimicrobial potency, a delicate matching between the positively charged units of polymers and the negatively charged units on the cell membranes of the pathogens should significantly improve the efficacy of antimicrobial polymers but without side effects on mammalian cells. However, the large pool of polymers for gene delivery established, majority of which are polyamines, can be explored for antimicrobial applications …”
Section: Discussionmentioning
confidence: 99%
“…For example, polyethyleneimines (PEI) were exploited to prepare glass slides with different surface chemistry and to evaluate their antiviral activity against influenza viruses. [ 30 ] Significant differences were found related to the length of the alkyl chains and the quaternization of amines. We would like to underline that the growing chemistry of 2D materials could find application in the development of antiviral coatings with ad hoc functional groups.…”
Section: Antiviral Surfaces and Coatingsmentioning
confidence: 99%